2021
DOI: 10.1186/s10195-021-00610-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic gluteus maximus tendon release for external snapping hip syndrome: a functional assessment

Abstract: Purpose The aim of this retrospective study was to investigate the clinical follow-up of patients with external snapping hip syndrome (ESHS) treated with endoscopic gluteus maximus tendon release and to compare the residual muscular strength and thigh circumference as an indirect outcome measure. Methods Patients of all ages with external snapping hip syndrome were treated with endoscopic gluteus maximus tendon release. Outcome measures evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…1,5 The technique for ITB release used in the study of Maldonado et al 4 seems more aggressive. Although a recent study revealed no functional or strength impairment after GMT release in patients with symptomatic ESH, 12 the authors confirmed a significant reduction in limb circumference compared with the contralateral side (3.7%). It is unclear whether this technique, composed of a transverse incision in the ITB and GMT release, will have an adverse effect on the involved hip, such as reduced extension and external rotation strength of the GM and reduced abductive strength of the abductors.…”
Section: See Related Article On Page 1890mentioning
confidence: 84%
“…1,5 The technique for ITB release used in the study of Maldonado et al 4 seems more aggressive. Although a recent study revealed no functional or strength impairment after GMT release in patients with symptomatic ESH, 12 the authors confirmed a significant reduction in limb circumference compared with the contralateral side (3.7%). It is unclear whether this technique, composed of a transverse incision in the ITB and GMT release, will have an adverse effect on the involved hip, such as reduced extension and external rotation strength of the GM and reduced abductive strength of the abductors.…”
Section: See Related Article On Page 1890mentioning
confidence: 84%
“…Various surgical techniques for the treatment of ESHS have been reported in the literature, including Z- or N-plasty lengthening of the ITB [ 2 , 6 , 7 ], release or resection of a portion of the ITB [ 2 , 8 12 ], and release of the GM femoral insertion [ 1 , 13 , 14 ], all of which can be performed via either an open or endoscopic approach. A review by Randelli et al reported endoscopic techniques, as compared to open surgery to have fewer complications, lower recurrence rates, and better clinical and cosmesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%